INHIBITION OF POLYMERASE CHAIN REACTION BY LITHIUM CHLORIDE: Life Science-Botany - MAJAZ GANAIE, MASOOD; HASSAN QAZI, PARVAIZ; VERMA, VIJESHWAR; RESHI, ZAFAR; HUSSAIN BAKSHI, SAJAD (International Journal of Life Science and Pharma Research, 2012)
Polymerase chain reaction has revolutionized the field of molecular biology. However, the technique needs careful monitoring for proper utilization. In contrast to false positives less attention has been given to false negatives. In the present study the inhibitory role of LiCl on amplification with Taq DNA polymerase has been studied. It was found that 30 mM concentration of LiCl conclusively inhibits amplification in a 20 µL reaction. Further the use of several PCR enhancers like BSA, DMSO and tween 20 could not help to reverse the effect. The effect of LiCl inhibition was found to be more on longer amplicons than shorter ones. MgCl2 concentration up to 2.5 mM (in excess of 2.25 mM in positive or negative control) helped amplification to some extent; however, the quality of amplification was relatively poor.